Clinical Isolates of Pseudomonas aeruginosa Stimulate Interleukin 1 Beta and Tumour Necrosis Factor Alpha in Mice Lungs (World Journal of Experimental Biosciences, 2021)
Pseudomonas aeruginosa has the ability to stimulate the pro-inflammatory immune response in addition to causing infection. The current study aims to evaluate the effect of this bacteria on generating the pro-inflammatory immune response and whether this response can be short-term or long-term, as well as to identify the persistence of bacterial infection in the lungs of experimental mice. Here, P. aeruginosa (PAC) was isolated from sputum samples collected from patients suffering from acute respiratory tract infections. Experimental mice were given 108 c.f.u of P. aeruginosa intra-nasal (i.n.). The lungs were harvested at different time intervals (1, 2, 4, 24, 48h) to check the Interleukin (IL-)1 Beta (β) and tumor necrosis factor (TNF-) alpha (α) using Enzyme linkage immune sorbent assay (ELISA) and (4, 24, 48, 72h) for studying the bacterial burden in mice lung using plate count method. Significant increase in IL-1B with maximum level by 4 h post instillation. A similar finding was observed in studying the level of TNF-a. In both cytokines, a significant increase was observed up to 48 h post-instillation with P. aeruginosa. The study showed that the clinical isolate of P. aeruginosa could be persistent up to 72 h post-instillation with PAC. The current study confirms the ability of this bacteria to stimulate the pro-inflammatory cytokines for a long period, as well as its ability to remain in the lungs of animals for long periods, which confirms the ability of the bacteria to maintain its negative effect for long periods in experimental animal lungs.